Dual Vertically Aligned Electrode‐Inspired High‐Capacity Lithium Batteries. Issue 30 (23rd August 2022) - Mu, Yongbiao; Chen, Yuzhu; Wu, Buke; Zhang, Qing; Lin, Meng; Zeng, Lin
Abstract: Lithium (Li) dendrite formation and poor Li + transport kinetics under high‐charging current densities and capacities inhibit the capabilities of Li metal batteries (LMBs). This study proposes a 3D conductive multichannel carbon framework (MCF) with homogeneously distributed vertical graphene nanowalls (VGWs@MCF) as a multifunctional host to efficiently regulate Li deposition and accelerate Li + transport. A novel electrode for both Li|VGWs@MCF anode and LFP|VGWs@MCF (NCM811 |VGWs@MCF) cathode is designed and fabricated using a dual vertically aligned architecture. This unique hierarchical structure provides ultrafast, continuous, and smooth electron transport channels; furthermore, it furnishes outstanding mechanical strength to support massive Li deposition at ultrahigh rates. As a result, the Li|VGWs@MCF anode exhibits outstanding cycling stability at ultrahigh currents and capacities (1000 h at 10 mA cm –2 and 10 mAh cm –2, and 1000 h at 30 mA cm –2 and 60 mAh cm –2 ). Moreover, full cells made of such 3D anodes and freestanding LFP|VGWs@MCF (NCM811 |VGWs@MCF) cathodes with conspicuous mass loading (45 mg cm –2 for LFP and 35 mg cm –2 for NCM811 ) demonstrate excellent areal capacities (6.98 mAh cm –2 for LFP and 5.6 mAh cm –2 for NCM811 ). This strategy proposes a promising direction for the development of high‐energy‐density practical Li batteries that combine safety, performance, and sustainability. Abstract : Homogeneously distributed vertical graphene nanowalls with abundant exposed edges, as a highly conductive coating layer, are successfully fabricated on 3D multichannel carbon framework (VGWs@MCF), which can effectively regulate Li deposition and accelerate Li + ion transport. The dual vertically aligned architecture electrodes using VGWs@MCF offers significant boost in both ultrahigh rates and capacities (40 mA cm –2 and 40 mAh cm –2 ) for LMBs.